Broadly tunable photon-pair generation in a suspended-core fiber - Hammer, Jonas; Chekhova, Maria; Häupl, Daniel; Pennetta, Riccardo; Joly, Nicolas (Physical Review Research, 2020)
Nowadays fiber biphoton sources are nearly as popular as crystal-based ones. They offer a single spatial mode and easy integrability into optical networks. However, fiber sources lack the broad tunability of crystals, which do not require a tunable pump. Here, we report a broadly tunable biphoton source based on a suspended core fiber. This is achieved by introducing pressurized gas into the fibers hollow channels, changing the step index. The mechanism circumvents the need for a tunable pump laser, making this a broadly tunable fiber biphoton source with a convenient tuning mechanism, comparable to crystals. We report a continuous shift of 0.30 THz/bar of the sidebands, using up to 25 bar of argon.
CRIS-Team WoS Importer:2021-01-15

Dispersion engineering of Schott-SF6 photonic crystal fibres for nonlinear applications in the infrared - Joly, Nicolas; Jiang, X.; Pennetta, Riccardo; Hammer, Jonas; Babic, F.; Russell, Philip St. John (Optics InfoBase Conference Papers, 2019)
An empirical model for estimating the dispersion of solid-core Schott-SF6 photonic crystal fibre is presented. Finite element calculations and experimentally measured power-dependent spectra confirm the accuracy of the model.
CRIS-Team Scopus Importer:2019-07-09

Nanometer Precision Measurement of Submicron Fibers via Seeded Four-Wave-Mixing - Hammer, Jonas; Haupl, Daniel R.; Russell, Philip St. John; Joly, Nicolas (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We report non-destructive measurement of the diameter of submicron air-clad waveguides to nanometer precision, based on parametric amplification of a broadband seed signal. Ultrashort pump and seed pulses allow the diameter to be longitudinally resolved.
CRIS-Team Scopus Importer:2020-10-09

Optomechanical cooling and self-stabilization of a waveguide coupled to a whispering-gallery-mode resonator - Pennetta, Riccardo; Xie, Shangran; Zeltner, Richard; Hammer, Jonas; Russell, Philip St. John (Photonics Research, 2020)
Laser cooling of mechanical degrees of freedom is one of the most significant achievements in the field of optomechanics. Here, we report, for the first time to the best of our knowledge, efficient passive optomechanical cooling of the motion of a freestanding waveguide coupled to a whispering-gallery-mode (WGM) resonator. The waveguide is an 8 mm long glass-fiber nanospike, which has a fundamental flexural resonance at Ω/2Π = 2.5 kHz and a Q-factor of 1.2 × 105. Upon launching ∼250 μW laser power at an optical frequency close to the WGM resonant frequency, we observed cooling of the nanospike resonance from room temperature down to 1.8 K. Simultaneous cooling of the first higher-order mechanical mode is also observed. The strong suppression of the overall Brownian motion of the nanospike, observed as an 11.6 dB reduction in its mean square displacement, indicates strong optomechanical stabilization of linear coupling between the nanospike and the cavity mode. The cooling is caused predominantly by a combination of photothermal effects and optical forces between nanospike and WGM resonator. The results are of direct relevance in the many applications of WGM resonators, including atom physics, optomechanics, and sensing.
CRIS-Team Scopus Importer:2020-06-16

Pressure-tuned phase-matched generation of non-classical light in microstructured fibre - Joly, Nicolas; Hammer, Jonas; Pennetta, R.; Cavanna, A.; Chekhova, Maria (23RD OPTO-ELECTRONICS AND COMMUNICATIONS CONFERENCE (OECC2018), 2018)
CRIS-Team WoS Importer:2019-08-13

Progress toward third-order parametric down-conversion in optical fibers - Cavanna, Andrea; Hammer, Jonas; Okoth, Cameron; Ortiz-Ricardo, Erasto; Cruz-Ramirez, Hector; Garay-Palmett, Karina; U'Ren, Alfred B.; Frosz, Michael H.; Jiang, Xin; Joly, Nicolas; Chekhova, Maria (Physical Review A, 2020)
Optical fibers have been considered an optimal platform for third-order parametric down-conversion since they can potentially overcome the weak third-order nonlinearity by their long interaction length. Here we present, in the first part, a theoretical derivation for the conversion rate both in the case of spontaneous generation and in the presence of a seed beam. Then we review three types of optical fibers and we examine their properties in terms of conversion efficiency and practical feasibility.
CRIS-Team WoS Importer:2020-04-10

Recent experimental results and future directions of the DLA single grating project - McNeur, Joshua; Hammer, Jonas; Li, Ang; Tafel, Alexander; Hommelhoff, Peter; Tafel, Alexander; Hammer, Jakob (16th Advanced Accelerator Concepts Workshop, AAC 2014, 2016)
The recent demonstration of Dielectric Laser Acceleration of subrelativistic electrons is reviewed. In this experiment, a Ti:Sapphire laser is incident upon a fused silica grating, exciting fields that accelerated 28 keV electrons with a 25 MeV/m acceleration gradient. Upgrades and future directions of this DLA project are discussed.